A Christoscopic Reading of Scripture: Johannes Oecolampadius on Hebrews - Fisher, Jeff (Vandenhoeck & Ruprecht, 2016)
***Angaben zur beteiligten Person Fisher: Jeff Fisher, PhD, is Assistant Professor of Theological Studies at Kuyper College, Grand Rapids, USA.
Keywords: Oekolampad, Johannes -- 1482-1531; Bibel -- Hebräerbrief; Christozentrik; Exegese; Hochschulschrift